Topical issues of protecting children from cyberbullying (Journal of actual problems of jurisprudence, 2022)
In this article, the author raises the problems of countering cyberbullying against children. Minors are active users of various communication Internet networks. Today, children's leading communication and socialization processes are moving to the Internet space, where they can hide their identity behind fictional avatars - anonymous masks. In many ways, this possibility of hiding your identity and sending anonymous messages increases the level of aggression in communication. Bullying in the Internet space manifests itself in the form of insults and the spread of slanderous rumours. Children who have become victims of bullying receive severe mental trauma and hard going through exclusion from society of their peers. Inattention to the problem of cyberbullying on the part of adults and failure to provide timely assistance and support can lead to severe consequences such as the suicide of a child. Prevention of bullying and cyberbullying, elimination of the contributing causes and conditions, bringing to justice those responsible in case of committing acts that violate the law – all this requires combining the actions of psychologists, representatives of law enforcement agencies, educational and other social organizations, parents and legal guardians of minors. Abroad, where the problem of bullying has long been recognized, there are specialized programs to counteract this negative phenomenon. The author refers to the results of such programs, examines foreign experts' research, and draws conclusions about the motives of aggressive behaviour and specific types of bullying. Based on the analysis, the author substantiates his proposals on ways to counter cyberbullying against children and improve law enforcement activities aimed at ensuring children's information security. Keywords: information security, Internet space, bullying, child bullying, cyberbullying, social networks.